Scaling Topic Maps Third International Conference on Topic Map Research and Applications, TMRA 2007 Leipzig, Germany, October 11-12, 2007 Revised Selected Papers - Maicher, Lutz; Garshol, Lars Marius (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International Conference on Topic Map Research and Applications, TMRA 2007, held in Leipzig, Germany in October 2007. The 16 revised full papers and 4 revised short papers presented together with 1 invited paper and 1 keynote lecture were carfully reviewed and selected from 44 submissions. The papers are organized in topical sections on applied topic maps in industry and administration, visualisation and representation of topic maps, collaborative applications, standards related research, information integration with topic maps, social software with topic maps, topic maps engines, topic maps and dublin core, information management with topic maps, as well as open space and poster sessions.